Fairness in Disability Crimes Against the Law - Bello, Yoel; S, Sudirman; Hijrah, Aswandi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The main idea of the Theory of Justice as fairness was developed by John Rawls, a theory of justice that generalises and raises the traditional concept of social contract to a higher level of abstraction, Rawls' theory is similar to the classical contract because it also starts from a kind of natural state, justice as fairness states that the law must create an ideal society, namely a society that tries to increase happiness and minimise unhappiness (the greatest happiness of the greatest number of people). The purpose of this study is to offer the theory of justice as fairness to law enforcers in the legal process of disabilities who are in conflict with the law. This research uses normative research. The approach used in this research includes a conceptual approach. The results of this study can be concluded that the application of law enforcers regarding fairness Justice, namely the principle for the basic structure of society is recognised as the first principle, then the principle for individuals, then followed by the principle of national law. So finally the priority rules are used. to create a fairer and more balanced criminal case settlement agreement for disabilities dealing with the law.